Major Earthquakes of Southern Calabria, Italy, Into the Regional Geodynamic Context - Neri, Giancarlo; Orecchio, Barbara; Scolaro, Silvia; Totaro, Cristina (Frontiers in Earth Science, 2020)
We analyze the seismicity of southern Calabria, the most active area of Italy from the seismic point of view, and compare it with geodetic data available from literature. Our analysis focuses both on the strongest earthquakes of the last centuries reported in the Italian seismic catalog and on seismicity recorded in the last decades by instrumental networks. The data highlight that strong shallow seismicity of southern Calabria, imputed to normal faulting by previous investigators, corresponds to low values of local, geodetic horizontal strain rate. This situation is quite different from that observed along the Apennines from Umbria to northern Calabria, where normal-faulting strong earthquake activity corresponds to relatively large values of extensional strain rate. On the other hand, the strong earthquake activity of southern Calabria corresponds to marked variation of vertical displacement rates detected from west to east in the same area. We frame these evidences into the regional geodynamic model assuming the coexistence of Africa-Europe NNW-trending plate convergence and SE-ward residual rollback of the Ionian lithospheric slab subducting underneath the Tyrrhenian-Calabria unit. Taking also benefit from the recently found relationship between the two strongest earthquakes of the twentieth century in Italy (the southern Calabria earthquakes of 1905 and 1908 of magnitude 7.5 and 7.1, respectively), we propose that instabilities of the upper bending part of the subduction slab may perturb shallow normal faults in the overriding plate and concur to shallow seismicity of southern Calabria jointly with the dynamics of differential vertical motion marked by geodetic data. The opposite action of lithosphere convergence and rollback may justify low values of horizontal strain rate in the low coupling scenario of the Ionian and Tyrrhenian-Calabria units.